THU0277 Evaluation of Polymorphisms of STAT4, TRAF31P2 and HCP5 in Sjögren Syndrome: Association with Disease Susceptibility and Clinical Aspects. (15th July 2016) - Colafrancesco, S.; Perricone, C.; Priori, R.; Picarelli, G.; Ciccacci, C.; Borgiani, P.; Latini, A.; Novelli, G.; Valesini, G.
Abstract : Background: Primary Sjögren syndrome (pSS) is a systemic inflammatory condition characterized by lymphocytic infiltrates in exocrine glands. STAT4 is one of the genes involved in "interferon (IFN) signature" and a single nuclear polymorphism (SNP), rs7574865 has been found associated with pSS. Other SNPs in TRAF3IP2 (rs33980500 and rs13193677) and HCP5 (rs3099844) genes, have been previously associated with the susceptibility to systemic lupus erythematosus (SLE), and seem to influence the disease phenotype. Objectives: To evaluate the association of different SNPs [STAT4 (rs7574865), TRAF3IP2 (rs33980500), HCP5 (rs3099844)] with the susceptibility to pSS and their role in modulation of clinical and laboratory features. Methods: One hundred thirty-five consecutive patients with pSS (AECC) were enrolled and clinical and laboratory data collected. Three hundred age and sex-matched healthy subjects were used as controls. Genomic DNA was isolated from peripheral blood mononuclear cells (Qiagen blood DNA mini kit). Genotyping was performed by allelic discrimination assays (Applied Biosystems, Foster City, CA, USA). Results: Clinical and laboratory features are reported in table. Deviations from Hardy–Weinberg equilibrium were not observed. The SNPs rs7574865 of STAT4 and rs3099844 of HCP5 were found associated with pSS at both the genotypic and allelic level (p<0.001, OR=1.84, 95%CI=1.28–2.65 and p<0.05, OR=2.28, 95%CI=1–3.7, respectively) and the data was confirmed after adjustment for other variables. STAT4 was found associated with the presence of monoclonal component (p=0.021). HCP5 was associated with the presence of leukopenia (p=0.021, OR=2.91, 95%CI=1.15–7.38) and lymphoma (p<0.001). Conclusions: This study confirms the association between the rs7574865 polymorphism of STAT4 and the susceptibility for pSS, and shows for the first time the association with a variant of HCP5. STAT4 was associated with monoclonal component supporting the role of IFN signature in autoantibodies production. Furthermore, HCP5 seem to be able to influence the disease phenotype predisposing to the development of leukopenia and lymphoma. These data need to be validated on larger cohorts of patients. Disclosure of Interest: None declared